Senior High School Students’ Higher Order Thinking Skills in Solving Combinatorics Problems - Arif Fatahillah; Vahad Agil Liyandri; Lioni Anka Monalisa (Universitas Sriwijaya, 2022)
Higher Order Thinking Skills (HOTS) refer to students' ability to solve problems by analyzing, evaluating, and creating. HOTS are essential for 21st century learning. Solving combinatorics problem troubleshooting requires HOTS. The aim of this research is to examine of senior high school students’ higher order thinking skills in solving combinatorics problems. This descriptive research describes the analysis of senior high school students’ higher order thinking skills in solving combinatorics problems. Class XII IPA 6 SMA Negeri 1 Trenggalek has a total of 21 students. Data was collected through a written test containing combinatorics problems and interviews. The results of the study show the senior high school students’ higher-order thinking skills in solving combinatorics problems: 38% of the students have